Handbook on Securities Statistics : Debt Securities Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Several high-level international groups urged development of methodological standards for securities statistics. In response, the Bank for International Settlements (BIS), the European Central Bank (ECB), and the International Monetary Fund (IMF) jointly developed the Handbook on Securities Statistics. The Handbook is the first publication that deals exclusively with the conceptual framework for the compilation and presentation of relevant, coherent, and internationally comparable securities statistics. Part I of the Handbook covers debt securities issues. Other parts are under development and cover issues of other types of securities and securities holdings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet